STRUKTUR DAN POLA KEPEMIMPINAN KYAI DALAM PESANTREN DI JAWA - Fadhilah, Amir (Institut Agama Islam Negeri (IAIN) Palu, 2011)
Abstract: The world of pesantren and the IslamicÂ clericsâÂ charisma Â is one of theÂ interesting phenomenaÂ toÂ be studied. The styleÂ ofÂ clericsâ lifeÂ andÂ religious studentsÂ is so great that it makes Islamic boardingÂ school posess a multi-dimensionalÂ function: The KyaisÂ notÂ only are not only required asÂ priestsÂ in religiousÂ ceremoniesÂ and ritualsÂ , butÂ also oftenÂ requiredÂ her presence Â toÂ resolveÂ the caseÂ or the difficultiesÂ that Â befallÂ the community.Â InÂ this context,Â the role of the Islamic clericsÂ is increasingly rootedÂ inÂ the communityÂ whenÂ their presencesÂ are believedÂ to bring fortune.Â The existence ofÂ structuresÂ andÂ patterns ofÂ authorityÂ (leadership) clericsÂ in the IslamicÂ worldÂ remainÂ sustainable,Â becauseÂ the Islamic clericsÂ haveÂ internal socialÂ netsÂ (among Â theÂ religious schools)Â and Â externalÂ social netwoeks (withÂ the world Â Â outsideÂ pesantren),Â includesÂ genealogicalÂ network, Â ideological network, Â intellectualÂ network, theologicalÂ network, and spiritualÂ network.Kata Kunci: pola kepemimpinan kyai, pesantren, kharismatik dan jaringan